An experimental investigation and modeling of micro array replication with Zr-based bulk metallic glass using a hot embossing process. (June 2017) - Zhang, Xiang; Luo, Yongsheng; Li, Junfeng; Dun, Bowen; He, Shiyang; Yan, Shujie; Li, Qian
Abstract: Zirconium-based bulk metallic glass (Zr-based BMG) is a potential material for micro/nano molds. In this study, we investigated the flow characteristics of Zr-based BMG in the supercooled liquid region (SLR) with a series of uniaxial compression tests. The Newtonian viscosity model of Zr-based BMG is constructed by fitting with the experimental results based on the Arrhenius equation. The hot embossing process which can be seen as a combination of two kinds of simultaneous flows is theoretically analyzed based on Navier-Stokes (N-S) equations. The velocity and pressure fields in a BMG sample have been evaluated. Two kinds of filling modes are proposed considering the interfacial tension and oxide layer that forms on the BMG surface. The exact solutions are obtained when the cavities of the micro arrays are circular, triangular and rectangular in shape based on N-S equations. The theoretical solutions, considered surface resistance, are in good agreement with our experimental results. These models can be used to describe the fillings of metallic glass in micro hot embossing process. Finally, we studied the effects of micro cavity size and shape on BMG filling, and found that the cavities of micro rectangular array are easier filling in same feature size, however, the cavities of micro circular array are easier filling in same area. The exact models developed in this paper can be used to calculate the BMG filling heights in the cavities of micro arrays and verify the reliability of simulation results in future mold designs. Highlights: Newtonian viscosity model of Zr-based BMG in SLR is constructed by fitting with experimental results. Micro hot embossing is theoretically analyzed based on Navier-Stokes equations. Exact solutions are deduced as the micro cavities are circular, triangular and rectangular. Two kinds of filling modes are proposed considering interfacial tension and oxide layer on BMG surface. The effects of size and shape of micro cavity on Zr-based BMG filling are found.